A pilot study to assess mediastinal emphysema after esophageal endoscopic submucosal dissection with carbon dioxide insufflation - Maeda, Y.; Hirasawa, D.; Fujita, N.; Obana, T.; Sugawara, T.; Ohira, T.; Harada, Y.; Yamagata, T.; Suzuki, K.; Koike, Y.; Yamamoto, Y.; Kusaka, Z.; Noda, Y. (Endoscopy, 2012)
Background and aims: Mediastinal emphysema sometimes develops following esophageal endoscopic submucosal dissection (ESD) without perforation because the esophagus has no serosa. Carbon dioxide (CO2) insufflation during esophageal ESD may reduce the incidence of mediastinal emphysema. The aim of the present study was to compare the incidence and severity of post-ESD mediastinal emphysema in patients receiving CO2 insufflation vs. standard air insufflation during esophageal ESD.Patients and methods: A total of 27 patients who had undergone esophageal ESD with insufflation of CO2 between July 2009 and March 2010 were enrolled in this study (CO2 group). Another 105 patients who had undergone esophageal ESD with air insufflation between March 2004 and May 2009 were included as historical controls (air group). Multi-detector row computed tomography (MDCT) was carried out immediately after ESD. A conventional chest radiograph was taken the next day. Mediastinal emphysema findings on MDCT and radiography were compared between the groups.Results: Mediastinal emphysema detected by chest radiography was 0 % in the CO2 group vs. 6.6 % in the air group (n.s.). Mediastinal emphysema on MDCT was significantly less frequent in the CO2 group compared with the air group (30 % vs. 63 %; P = 0.002). The severity of mediastinal emphysema also tended to be lower in the CO2 group.Conclusions: Whereas mediastinal emphysema detected by radiography is not so common, MDCT immediately after ESD revealed a certain prevalence of post-ESD mediastinal emphysema. Insufflation of CO2 rather than air during esophageal ESD significantly reduced postprocedural mediastinal emphysema. CO2 can be considered as insufflating gas for esophageal ESD.